2017
DOI: 10.3928/01477447-20170223-03
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomy of the Medial Patellofemoral Ligament

Abstract: Recurrent patellar dislocation is observed in many patients treated nonoperatively following primary dislocation. Injury to the medial patellofemoral ligament (MPFL) is reported in the majority of patients following dislocation. There is an increased interest in repair or reconstruction of the MPFL for patients experiencing recurrent instability. The femoral attachment of the MPFL is critical in determining graft behavior following reconstruction. The femoral attachment can be determined by referencing local a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The saddle sulcus has been anatomically 3 , 58 , 60 and radiographically 11 identified as an osseous depression or region where the MPFL is consistently attached. Considering previous descriptions of the MPFL femoral footprint, 1 , 21 , 24 , 48 , 52 we thus determined the saddle sulcus on the reconstructed femur as (1) being located within the boundaries of the AT, ME, and MGT; (2) lying posterior to the border connecting the apexes of the AT and ME; and (3) a broad, oblong, and oblique saddle-like sulcus. The 3D-reconstructed model was rotated to ultimately determine the presence of the saddle sulcus.…”
Section: Methodsmentioning
confidence: 99%
“…The saddle sulcus has been anatomically 3 , 58 , 60 and radiographically 11 identified as an osseous depression or region where the MPFL is consistently attached. Considering previous descriptions of the MPFL femoral footprint, 1 , 21 , 24 , 48 , 52 we thus determined the saddle sulcus on the reconstructed femur as (1) being located within the boundaries of the AT, ME, and MGT; (2) lying posterior to the border connecting the apexes of the AT and ME; and (3) a broad, oblong, and oblique saddle-like sulcus. The 3D-reconstructed model was rotated to ultimately determine the presence of the saddle sulcus.…”
Section: Methodsmentioning
confidence: 99%
“…This distance has been shown to be equivalent to the length of the intact native MPFL. 1 , 2 , 37 The tensile force applied to the graft was in the line of pull parallel to the SA or TS, in accordance with the “worst-case scenario” for graft testing. We first applied a preload of 5 to 20 N for 10 cycles to reduce any tissue hysteresis.…”
Section: Methodsmentioning
confidence: 99%
“… 17 , 18 , 40 , 42 Biomechanical studies have demonstrated that the medial patellofemoral ligament (MPFL) is the primary soft tissue that prevents lateral patellar displacement. 1 , 2 , 8 , 13 , 37 Recently, MPFL reconstruction has gained attention because it has yielded good results in clinical trials involving patients in whom nonoperative treatment for recurrent patellar instability has failed. §…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…33 Although there is ongoing discussion of the exact site of ligamentous origin, generally speaking the MPFL runs from the medial femoral epicondyle to the superior one-third or one-half of the medial edge of the patella. 34 On MRI, a normal MPFL is seen as a low signal, linear structure that blends with the vastus medialis obliquus (VMO) muscle, often best depicted on axial images at the distal-most aspect of the VMO. It can be difficult to distinguish between the MPFL and patellar retinaculum, which follows a similar course but is more inferior, attaching to the proximal tibia.…”
Section: Medial Patellofemoral Ligament Normal Imaging Appearancementioning
confidence: 99%